Further records of Amphipoda from Baltic Eocene amber with first evidence of prae-copulatory behaviour in a fossil amphipod and remarks on the taxonomic position of Palaeogammarus Zaddach, 1864 - Jażdżewski, Krzysztof; Grabowski, Michał; Kupryjanowicz, Janusz (Zootaxa, 2014)
Two pieces of Baltic amber with amphipod inclusions were studied. One of them contained approximately twenty individuals identified as belonging to the extinct genus Palaeogammarus and described as P. debroyeri sp. nov. Interestingly, among the individuals there are two pairs preserved in an evident prae-copula position. This is the first finding of such mating behaviour in fossil amphipods. Based on this behavioural trait and on the observed morphological features, we conclude that the genus Palaeogammarus should be placed in Gammaridae and not in Crangonyctidae. The second amber piece contains two individuals identified as belonging to the still extant genus Synurella and described as S. aliciae sp. nov.